Integration Questions

Question Number 173486 by mnjuly1970 last updated on 12/Jul/22

$$\\$$$$\:\:\:\:\boldsymbol{\phi}\:=\:\int_{\mathrm{0}} ^{\:\infty} \frac{{cos}\:\left({ax}\right)β\:{sin}\left({bx}\right)}{{x}^{\:\mathrm{2}} }{dx}\:\:=? \\$$$$\:\:\: \\$$$$\:\:\:\boldsymbol{\phi}=\int_{\mathrm{0}} ^{\:\infty} \frac{\mathrm{1}β\mathrm{2}{sin}^{\:\mathrm{2}} \left(\frac{{ax}}{\mathrm{2}}\right)β\left(\mathrm{1}β\mathrm{2}{sin}^{\:\mathrm{2}} \left(\frac{{bx}}{\mathrm{2}}\right)\right)}{{x}\:^{\mathrm{2}} }{dx} \\$$$$\:\:\:\:\:\:\:=\mathrm{2}\:\left\{\int_{\mathrm{0}} ^{\:\infty} \left(\frac{{sin}\left(\frac{{bx}}{\mathrm{2}}\right)}{{x}}\right)^{\mathrm{2}} {dx}=\Theta_{\mathrm{1}} \right\}β\mathrm{2}\left\{\int_{\mathrm{0}} ^{\:\infty} \left(\frac{{sin}\left(\frac{{ax}}{\mathrm{2}}\right)}{{x}}\right)^{\mathrm{2}} {dx}=\Theta_{\mathrm{2}} \right\} \\$$$$\:\:\:\:\:\:\:\:\Theta_{\:\mathrm{1}} \overset{\frac{{bx}}{\mathrm{2}}={t}} {=}\:\frac{{b}}{\mathrm{2}}\int_{\mathrm{0}} ^{\:\infty} \frac{{sin}^{\:\mathrm{2}} \left({t}\right)}{{t}^{\:\mathrm{2}} }{dt}=\:\frac{\pi{b}}{\mathrm{4}}\: \\$$$$\:\:\:\:\:\:\:\:{similarly}\::\:\:\Theta_{\:\mathrm{2}} =\frac{\pi{a}}{\mathrm{4}}\:\:\:\:\:\therefore\:\:\:\boldsymbol{\phi}=\:\frac{\pi}{\mathrm{2}}\left(\mid{b}\midβ\mid{a}\mid\right)\: \\$$$$\:\:\:\:\:{Dirichlet}'{s}\:{integrals}:\:\int_{\mathrm{0}} ^{\:\infty} \frac{{sin}\left({x}\right)}{{x}}{dx}=\frac{\pi}{\mathrm{2}}=\int_{\mathrm{0}} ^{\:\infty} \frac{{sin}^{\mathrm{2}} \left({x}\right)}{{x}^{\:\mathrm{2}} }{dx} \\$$

Commented by mokys last updated on 15/Jul/22

$$\\$$$$\boldsymbol{\phi}\:\left(\boldsymbol{{a}}\right)=\:\int_{\mathrm{0}} ^{\:\infty} \:\frac{\boldsymbol{{cos}}\left(\boldsymbol{{ax}}\right)}{\boldsymbol{{x}}^{\mathrm{2}} }\:\boldsymbol{{dx}}\:\rightarrow\:\boldsymbol{\phi}^{'} \left(\boldsymbol{{a}}\right)\:=β\:\int_{\mathrm{0}} ^{\:\infty} \:\frac{\boldsymbol{{sin}}\left(\boldsymbol{{ax}}\right)}{\boldsymbol{{x}}}\:\boldsymbol{{dx}} \\$$$$\left(\boldsymbol{{ax}}\right)=\:\boldsymbol{{k}}\:\rightarrow\:\boldsymbol{{dx}}\:=\:\frac{\boldsymbol{{dk}}}{\boldsymbol{{a}}} \\$$$$\\$$$$\boldsymbol{\phi}^{'} \left(\boldsymbol{{a}}\right)\:=\:β\:\int_{\mathrm{0}} ^{\:\infty} \:\frac{\boldsymbol{{sink}}}{\boldsymbol{{k}}}\:\boldsymbol{{dk}}\:=\:β\:\frac{\boldsymbol{\pi}}{\mathrm{2}} \\$$$$\\$$$$\:\therefore\:\boldsymbol{\phi}\:\left(\boldsymbol{{a}}\right)\:=\:β\frac{\boldsymbol{{a}\pi}}{\mathrm{2}} \\$$$$\\$$$$\boldsymbol{\phi}\left(\boldsymbol{{b}}\right)\:=\:\int_{\mathrm{0}} ^{\:\infty} \:\frac{\boldsymbol{{sin}}\left(\boldsymbol{{bx}}\right)}{\boldsymbol{{x}}^{\mathrm{2}} }\:\boldsymbol{{dx}}\: \\$$$$\\$$$$\boldsymbol{{let}}:\:\boldsymbol{{bx}}\:=\:\boldsymbol{{m}}\:\rightarrow\:\boldsymbol{{dx}}\:=\:\frac{\boldsymbol{{dm}}}{\boldsymbol{{b}}} \\$$$$\\$$$$\boldsymbol{\phi}\left(\boldsymbol{{b}}\right)\:=\:\boldsymbol{{b}}\:\int_{\mathrm{0}} ^{\:\infty} \:\frac{\boldsymbol{{sin}}\left(\boldsymbol{{m}}\right)}{\boldsymbol{{m}}^{\mathrm{2}} }\:\boldsymbol{{dm}}\:=\:\frac{\boldsymbol{{b}\pi}}{\mathrm{2}} \\$$$$\\$$$$\therefore\:\boldsymbol{\phi}\:\left(\boldsymbol{{a}},\boldsymbol{{b}}\right)=\:\frac{\boldsymbol{\pi}}{\mathrm{2}}\:\left(\:\mid\boldsymbol{{b}}\midβ\mid\boldsymbol{{a}}\mid\:\right) \\$$$$\\$$$$\:\boldsymbol{{Aldolaimy}}\:\boldsymbol{{mohammad}} \\$$